(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Panchakarma is the fivefold purification procedure explained in Ayurveda. Langhana the broad spectrum of treatment comes under Dwividhaupakrama which consists of both Samana and Sodhana procedures. Sodhana mainly aims in the elimination of Doshas from the body and thus restore health and prevent the recurrence of diseases. Samana is the treatment were Doshas get pacified by different modalities of treatment. After Sodhana immediate decrease of digestive fire will occur which get restored in the Paschat karma. A specific dietetic schedule must be followed after Sodhana especially after Vamana and Virechana to improve Agni and Bala. This specific food regimen containing different types of meals in a specific order after Sodhana for a particular duration according to the grade of Sudhi is known as Samsarjana krama. Peyadikrama is the most popular and extensively implementing one in common clinical practice but in conditions of Kapha dominance after Sodhana, Peyadi will not work because of the Abhishyandi nature of Peya. In conditions of less eliminated Kapha-Pitta dosha, Tarpanadi krama (graduated nutritive dietetic protocol) should be adopted after Sodhana. It consists of Laja, Sakthu, Yusha and Mamsa rasa in sequential order. The first day of Tarpanadi krama is given with Laja a converted form of rice by the process of puffing provide instant energy by quick digestion and easy absorption. The person who belongs to vulnerable group such as child, old aged, pregnant women etc. and those are physically weak due to depleted Dhatu can be administered Tarpanadi krama after Sodhana therapy.